Familia y vida privada en la historia de Iberoamérica : seminario de historia de la familia - Gonzalbo, Pilar, 1935-; Rabell, Cecilia Andrea (Book collections on Project MUSE., 1996)
"Collection of 22 well-researched studies covers early colonial era into early-20th century. Many are based on archival research; all are thoroughly footnoted. A 43-page index enhances volume's value. Approximately half of the studies deal with Mexico"--Handbook of Latin American Studies, v. 58.